Assessment of water productivity and entry points for improvement in mixed crop-livestock systems of the Ethiopian highlands - Descheemaeker, Katrien K.; Haileslassie, Amare; Amede, Tilahun; Bossio, Deborah A.; Tarawali, Shirley A. (Elsevier, 2010)
Crop-livestock systems are very important both in terms of area and contribution to people’s livelihoods in the Ethiopian highlands. However, a common problem in these systems is low livestock and crop productivity, which is partly caused by water scarcity and environmental degradation. As water is a key and often limiting input for agriculture and environmental functioning, there is an urgent need to improve water productivity in order to sustain both people’s livelihoods and a healthy environment. Water productivity, generally defined as the ratio of agricultural outputs to the volume of water depleted, measures the ability of agricultural systems to convert water into food. In the crop sector, crop water productivity (CWP) has been investigated for many years. By contrast, livestock water productivity (LWP) is a new concept (Peden et al., 2009), for which reference points, standardized definitions and adequate methods for water partitioning are still in their infancy (Descheemaeker et al., 2010). Also, a systems approach for analyzing water productivity in mixed systems is still to be developed, tested and adapted. This paper therefore examines how water productivity can be assessed in mixed crop-livestock systems, and identifies entry points for water productivity improvement with the wider aim to improve the sustainability of the systems.